2018
DOI: 10.1532/hsf.1911
|View full text |Cite
|
Sign up to set email alerts
|

Increased Short-Term and Mid-Term Major Complications Were Observed in Elderly Patients with Renal Dysfunction after Surgical Ventricular Restoration

Abstract: Compared to patients with normal renal function, elderly SVR patients with renal failure have a higher incidence of short-term mechanical support, mid-term mortality, and MACCE events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A meta-analysis published in 2013 and including 49 studies, mostly in vascular and cardiac surgery, reported that eGFR less than 60 ml/min/1.73 m 2 was associated with a threefold increase in 30-day mortality risk for surgical patients 10 . A retrospective single-center study reported increased risks of postoperative all-cause mortality and major adverse events in elderly patients with preoperative renal dysfunction (defined as eGFR <60 ml/min/1.73 m 2 ) 17 .…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis published in 2013 and including 49 studies, mostly in vascular and cardiac surgery, reported that eGFR less than 60 ml/min/1.73 m 2 was associated with a threefold increase in 30-day mortality risk for surgical patients 10 . A retrospective single-center study reported increased risks of postoperative all-cause mortality and major adverse events in elderly patients with preoperative renal dysfunction (defined as eGFR <60 ml/min/1.73 m 2 ) 17 .…”
Section: Discussionmentioning
confidence: 99%